太阳能热动力储能系统 (2017)
本发明涉及种储能系统，具体的说是太阳能热动力储能系统，属于能量储存技术领域。其包括太阳能集热系统、压缩储能系统和热动力膨胀系统，通过光伏发电装置发电驱动高压压缩机工作，外部电能通过电站电网驱动高压压缩机和低压压缩机工作，通过膨胀机膨胀发电释放能量。本发明能够将电站电网低谷电能及白天太阳能光伏发电多余电量进行储能，充分利用太阳能光伏发电和阳光热动力储存热量发电，提高了能量的利用效率，降低了发电成本，提高了经济效益。 The invention relates to an energy storage system, in particular to a solar thermal dynamic energy storage system, belonging to the technical field of energy storage. The solar thermal dynamic energy storage system comprises a solar collecting system, a compressed energy storage system and a thermal power expansion system, wherein a photovoltaic power generation device can generate electricity to drive a high-pressure compressor to work, external electric energy can drive the high-pressure compressor and a low-pressure compressor to work through a power grid of a power station, and an expansion machine can swell to generate electricity to release energy. According to the energy storage system, the valley electric energy of the power grid of the power station and residual electric quantity generated throu